REVIEW OF WATER POLLUTION PREVENTION AT BITUNG FERRY PORT NORTH SULAWESI PROVINCE - Lopulalan, Pierre Marcello; Sari, Yulia Puspita; Apriani, Dahlia Dewi; Ambassador, Topaz Ramadan (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2023)
Environmental pollution is currently a disturbing issue for the survival of life, including in shipping and port activities, therefore the Ministry of Transportation issued PM Number 39 of 2021 and PM Number 24 of 2022. Based on conditions in the field, it is known that these regulations have not been complied with, such as pollution control tools and materials, port personnel competence, and fulfillment of pollution prevention on ships as evidenced by a Certificate approved by a classification body recognized and appointed by the Minister. The purpose of writing this mandatory working paper is none other than to determine the suitability of conditions in the field with existing regulations. The study used the method gap analysis that compares existing conditions with expected conditions according to regulations. Based on the results of data analysis and discussion of the problems, it was concluded that the prevention of water pollution at the Bitung Ferry Port is still not in accordance with PM Number 39 of 2021 and PM Number 24 of 2022, so that proposals are needed in efforts to prevent pollution in the waters, namely to procure pollution prevention tools and materials, improve the competence of pollution prevention for personnel, and fulfill pollution prevention by ships as evidenced by a certificate.